ANALISIS TEKNIS DAN PELUANG PENGEMBANGAN INOVASI TEKNOLOGI BIOFLOK UNTUK OPTIMALISASI PRODUKSI IKAN NILA (Oreochromis niloticus) BERKELANJUTAN: Technical Analysis And Development Opportunities For Biofloc Technology Innovations In Optimizing Sustainable Tilapia (Oreochromis niloticus) Production - Ayi Yustiati; Desi Sartika (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2026)
Tilapia (Oreochromis niloticus) cultivation still faces various obstacles, such as declining water quality and high production costs. Biofloc technology is one of the innovations that has the potential to increase the efficiency and productivity of cultivation in a sustainable manner. This research was conducted to analyze the technical aspects and opportunities for the development of biofloc technology in optimizing tilapia production. The purpose of the research is to get innovations in the development of optimal tilapia biofloc technology. The research method used is descriptive exploratory with a Systematic Literature Review (SLR) approach. The procedures for searching, article selection, data extraction, and reporting refer to the PRISMA 2020 27 item checklist. The results of the study show that there are four types of biofloc technology innovations in tilapia that are the most optimal, namely Biofloc without buffer media (Suspended-Growth systems), the integration of bioflocs with aquaponics systems and Recirculating Aquaculture Systems (RAS), and the application of the Internet of Things (IoT). The implementation of the tilapia biofloc innovation has a positive effect on increasing tilapia production in a sustainable manner.